IMPROVING QUALITY OF CARE IN THE MANAGEMENT OF PATIENTS WITH URINARY CATHETERS THAT ATTEND THE EMERGENCY DEPARTMENT. Issue 12 (18th November 2016) - Yeung, C; Krishnathasan, K; Chan, C; Blows, S; Cheah, K; Whitwell, K
Abstract : Objectives & Background: Patients presenting with catheter problems are a significant burden on the Emergency Department (ED). An initial audit was performed in 2014/15 which showed that the majority of these patients were elderly, arrived in working hours, did not need to see a specialist and were discharged after simple interventions. A number were also repeat attenders. Following this audit, a number of interventions were introduced. The equipment was reviewed to ensure that the correct catheters were used. Troubleshooting protocols for common catheter problems were placed on the catheter trolleys. Education regarding catheter problems was incorporated into the induction program for junior doctors. Three urology ED nurse champions were appointed. A multidisciplinary team was formed comprising geriatric, urology & ED consultants, with the aim of formulating solutions to tackle the rising burden of catheter patients. The audit was then repeated in 2015/16. Methods: This was a retrospective case note review of patients with a 'catheter problem'. They were identified through a manual search on our ED coding database. Data (e.g. age, time of arrival, admission rate, etc.) was first collected from Nov 14 to Feb 15. This was repeated from Nov 15 to Feb 16 after our interventions listed above. 24 'catheter problem' patients that presented in Oct 15 were also telephoned to evaluate patient satisfaction using a standardised questionnaire. Results: There were 5% fewer attendances and 28% fewer repeat attenders in 2015/16 despite a rise of 7% in the total no. of all ED attendances over the same time period. Again, majority of the patients were elderly, arrived in working hours (60%), and were discharged home from ED (83%). Only 13% needed a urological opinion. There were 18 phone responses out of 24 (75%). A going home catheter pack was given to all patients that needed them. The process of catherisation was explained to all patients. 100% of patients were satisfied with the ED service, with 67% awarding us a 6 (on a scale of 1 to 6, with 1 being not at all satisfied and 6 being very satisfied). Conclusion: We have improved the quality of care of patients with urinary catheters by ensuring correct initial management and good patient education. That has led to a subsequent reduction in patient attendances and re-attendances to the ED, as well as a high standard of care provided to those that did present in ED.Figure 1 Figure 2 Figure 3